Lesson study program evaluation for English teachers in Tidore - Idhar Hasan; Jean Antunes Rudolf Zico Ma’u (Universitas Sarjanawiyata Tamansiswa, 2019)
The objectives of this study are to 1) evaluate lesson study program for English teachers at SMP Negeri 1 Tidore based on context, input, process and product, 2) find out the effectiveness of lesson study program for English teachers at SMP Negeri 1 Tidore based on CIPP model evaluation. The research is an evaluation lesson study program for English teachers at SMP Negeri 1 Tidore based on CIPP model evaluation. The CIPP consist of Context, Input, Process, and Product. The data were collected through observation and in-depth interviews. The data were analyzed using descriptive and qualitative data analyses included data collection, data condensation, data display, and data conclusion drawing or verification based on theory of Miles, Huberman and Saldana (2004). The result of the study in terms of evaluation lesson study program for English teachers in the SMP Negeri 1 Tidore from context, input, process and product showed there was a need from English teachers to improve their professionalism competence. The government held lesson study program to achieve the goal that is to improve the English Teachers professionalism. The need supported by the input that the government provide everything needed by the English teacher to carry out lesson study program. The process of the implementing of lesson study program showed that program has been carrying out well. The output of the lesson study program, in terms effectiveness of lesson study program for English teachers at SMP Negeri 1 Tidore. This study showed that is program has affective enough in improving English teachers professionalism but there should be improvement in some parts. They are related to the schedule of teaching learning so the learners obtain much knowledge from the material given.